WHOSE PARADISE? CUSTOMARY FORESTS, TOURISM, AND POWER IN BALI - Darmawijaya, I Gede; Seniartha, I Wayan; Sunarsa, I wayan; Eka Darmaputra, Putu Gede; Todi Astawan, I Kadek (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2025)
This paper critically examines the contested relationship between customary forest management, sustainable tourism development, and inclusive leadership in Bali, Indonesia. Through a comparative case study approach, it analyzes the divergent outcomes of community-based conservation efforts. The first case focuses on the Tamblingan Lake region, where four villages (Catur Desa) strive to gain legal recognition of their customary forest (Merta Jati) against government-backed commercial interests. The second case, Tenganan Pegringsingan Village, provides a contrasting example of a successful, long-established customary forest management system integrated with cultural tourism, albeit with emerging challenges. This research uses a comparative case study approach to understand how inclusive leadership, traditional forest management, and sustainable tourism interact. The study combines qualitative data gathered from semi-structured interviews with villagers and social media content analysis. The findings emphasize that inclusive leadership is critical in resolving conflicts between local ecological knowledge, economic pressures from development, and policies imposed from above. The paper contributes to discussions on inclusive leadership, community-based natural resource management, and sustainable tourism. It also offers policy recommendations to create fairer and more environmentally responsible tourism development in culturally sensitive settings. It specifically addresses the need for legal frameworks recognizing customary rights and promoting genuine community participation in decision-making.